Development and validation of headspace Solid-Phase microextraction coupled with gas chromatography (HS-SPME-GC) method for the analysis of zingiber zerumbet L. Issue 7 (3rd April 2021) - Bhavya, M. L.; Ravi, R.; Madhava Naidu, M.
Abstract: Headspace solid-phase microextraction (HS-SPME) coupled with gas chromatography (GC-FID) was explored to determine the fingerprinting characteristic of Zingiber zerumbet L. volatiles to differentiate between different ginger species. The effect of different fibers [polydimethylsiloxane (PDMS, 7 μm), polyacrylate (PA, 85 μm)], different temperature and time on the HS-SPME-GC was investigated by using response surface methodology coupled with full factorial experimental design. The area percentage of the major sesquiterpenes (Zerumbone and α-humulene) were 56.3 ± 4.7% and 47.5 ± 27.2% with PA fiber, respectively at optimum condition of 70 °C and 30 min. Validation of the developed HS-SPME-GC method with limits of detection and quantification for zerumbone was 0.09 and 0.28 μg/g, respectively, demonstrating the suitable sensitivity of HS-SPME-GC method for the quantification of sesquiterpenes. Therefore, the simplicity of HS-SPME-GC makes it a convenient tool for qualitative and quantitative comparison of different ginger species targeting at the marker sesquiterpene molecule, zerumbone. Abstract :